Incidencia del salario mínimo y el desempleo en el salario real, una estimación de la ecuación de la renta para Ecuador en el periodo 2007-2022 - Jaramillo Rojas, Janela Elizabeth (2022)
Although Ecuador has one of the highest salaries rates in Latin America, it does not fully satisfy the needs of the population; the objective of this research is to determine the fulfillment of the salary equation by means of a cointegration model for Ecuador in the period 2007-2022; additionally, the gap between the salaries of the poorest and the wealthiest was evaluated; the results indicate that in Ecuador the salary equation is fulfilled, that is, unemployment has a determinant incidence on salaries. It was also found that the minimum wage had a positive effect in the short-term, but not in the long-term relationship; likewise, high inflation rates end up deteriorating the purchasing power of people. In the case of the income gap, it was found that the richest quintile has 57.21% of the income. Among the policy recommendations we’ve included the stimulation by the State of job-creating investment, flexibility in hiring in the event of an increase in unemployment, and credits for the agricultural sectors with the intention of increasing supply and maintaining constant prices.